Mediating effect of self-efficacy in the relationship between technology competency and learners' acceptance and usage of e-learning portal - Raemah, Abdullah Hashim; Noryati, Alias (2015)
The purpose of this study is to investigate the mediating effect of self-efficacy in the relationship between technology competency and learners’ acceptance and usage of e-learning portal among adult learners in one private university in Malaysia. The sample consists of 153 adult learners from various business programmes. Structural Equation Modeling (SEM),employing AMOS 22 was used to test the mediation effect and also the relationship between technology competency of learners with learners’ acceptance and usage of the e-learning portal. A non-significant relationship was found between technology competency with learners’ acceptance and usage of the e-learning portal. However, when the mediation hypothesis was tested, the result indicates that self-efficacy fully mediates the relationship between technology competency and learners’ acceptance and usage of the e-learning portal.